The Revitalization of Iconic Shapes through the Creation of Relief Dimensional Paintings as Tourism Software Products (Case Study in Medan City, Indonesia) - Zulkifli Zulkifli; Anam Ibrahim; Mangatas Pasaribu; Bakhrul Khair Amal (RIRAI Publisher, 2021)
Medan City in Indonesia, is rich with iconic forms in the form of historical buildings and cultural products of the past. On the other hand, Medan City tourism has been known since the Dutch colonial era, but has not been supported by the availability of souvenir products. This research article describes the revitalization of the iconic forms of Medan City. The aim is to examine the potential of iconic forms to be used as the basis for the development of relief-dimensional painting as a tourism souvenir product. This research use desciptive qualitative approach. The replicated method is a combination of survey method and creation method. Sources of research data are written data, photo data, interview results, notes on the creation process, and appreciative assessments. Data analysis was carried out using an interactive model: data reduction, data presentation, verification and conclusion drawing. The results showed that the iconic shapes of Medan City have great potential to be explored into original painting themes. Technically, the art of painting with relief dimensions is effectively developed with rubber sheet material, supported by strong texture work. Overall, the paintings produced have an aesthetic quality, exclusive as tourism souvenirs.